Mass‐Dependent Integral Curves in Unsteady Vector Fields. (1st July 2013) - Günther, Tobias; Kuhn, Alexander; Kutz, Benjamin; Theisel, Holger
Abstract: Recent research in flow visualization is focusing on the analysis of time‐dependent, but mass‐less particles. However, in many application scenarios, the mass of particles – and their resulting inertia – is essential in understanding fluid mechanics. This includes critical processes, such as dust particles interacting with aircraft (e.g., brown‐or white‐out effects) and particle separation based on density variation. In this paper, we contribute a generalized description of mass‐dependent particle trajectories and apply existing unsteady flow visualization methods to the mass‐dependent case. This comprises the extension of common concepts, i.e., path lines, streak lines, and time lines. Furthermore, we introduce a new class of integral curves, called mass lines that effectively visualizes mass separation and captures mass‐related features in unsteady flow fields that are inaccessible using traditional methods. We demonstrate the applicability of our method, using a number of real‐world and artificial data sets, in which mass is a crucial parameter. In particular, we focus on the analysis of brown‐out conditions, introduced by a helicopter in forward flight close to the ground.